2015
DOI: 10.1007/s00590-015-1633-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive fixation of midclavicular fractures with threaded elastic intramedullary nails

Abstract: Treatment Study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Another type of fixation described was the Sonoma CRx (Arthrex, Naples, FL, USA) for which 6 studies (three level I, [67][68][69] one level II, [70] one level III [71] and one level IV [72]) were identified. Less frequently described intramedullary fixation devices were the threaded titanium elastic nails (Kang Li Min Medical Devices Co. Ltd., Tianjin, China), [73][74][75] the Knowles pin (Zimmer Biomet, Warshaw, IN, USA) [76][77][78][79] and one study describing a second generation Titanium elastic nail (Puwei Medical Appliances Inc., Shanghai, China) [80]. Table 1 displays study characteristics including population description, type of intramedullary device, functional outcome scores, and type and number of complications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another type of fixation described was the Sonoma CRx (Arthrex, Naples, FL, USA) for which 6 studies (three level I, [67][68][69] one level II, [70] one level III [71] and one level IV [72]) were identified. Less frequently described intramedullary fixation devices were the threaded titanium elastic nails (Kang Li Min Medical Devices Co. Ltd., Tianjin, China), [73][74][75] the Knowles pin (Zimmer Biomet, Warshaw, IN, USA) [76][77][78][79] and one study describing a second generation Titanium elastic nail (Puwei Medical Appliances Inc., Shanghai, China) [80]. Table 1 displays study characteristics including population description, type of intramedullary device, functional outcome scores, and type and number of complications.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis was only possible for infection [73][74][75] and the pooled incidence was 5% (95%CI 1-34 in 106 clavicles).…”
Section: Studies Concerning a Threaded Elastic Nailmentioning
confidence: 99%
“…1) [57,58] one level II, [59] one level III [60] and one level IV [61]) were identified. Less frequently described intramedullary fixation devices were the threaded titanium elastic nails (Kang Li Min Medical Devices Co. Ltd., Tianjin, China), [62][63][64] the Knowles pin (Zimmer Biomet, Warshaw, IN, USA) [65][66][67][68] and one study describing a second generation Titanium elastic nail (Puwei Medical Appliances Inc, Shanghai, China).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on persistent pain as a complication [58,60] and 1 study mentions the occurrence of a delayed union. [57] Studies concerning a threaded elastic nail Meta-analysis was only possible for infection [62][63][64] and the pooled incidence was 5% (95%CI 1-34).…”
Section: Meta-analysismentioning
confidence: 99%
“…Studies suggested that intramedullary fixation is a more advantageous method for the treatment of mid‐shaft clavicle fractures, achieving excellent aesthetic and early recovery after surgery. For intramedullary fixation, the most common devices in clinics used are Knowles pinning, elastic stable titanium intramedullary nailing, Rockwood clavicle pin, Acumed clavicle rod, Hagie pin, expandable elastic locking intramedullary nail and threaded elastic intramedullary nail. All these devices have their own merits and demerits.…”
Section: Introductionmentioning
confidence: 99%